Valores éticos e estéticos na formação ambiental em trilha ecológica: promoção e investigação de atividades para trilhas educativas no Cerrado associadas à tecnologia - Ghidini, Milena Sciascio (2022)
The present study had as guiding themes the Environmental Education and the technology associated with Environmental Education. Themes that were thought based on a systemic and integrated vision of human beings with the environment and with other living beings on the planet. The general objective of this study was to investigate conceptions, practices and approaches about values in Environmental Education in ecological educational trails, aiming to establish specific instruments, which were evaluated. To support the reflections brought into this study, the Environmental Education approach was adopted, according to Carvalho (2006), with an integrated and complex view of interconnected dimensions in participation and citizenship, knowledge and ethical and aesthetic values. In order to achieve the proposed objectives, we were based on qualitative and applied research, by means of (interviews with members of the extension project, specialists in related areas and with people responding to the application/technology evaluation questionnaire. These instruments allowed the collection of data and information, analyzed through techniques based on and inspired by discursive textual analysis (DTA). The main results of this dissertation were generated throughout: a script of proposed activities applied in educational ecological contexts; a script integrated to the application developed by Startup Fubá - Environmental Education and evaluation of the use of this application. It is concluded that there should be a greater integration between the themes in the values dimension and Environmental Education, in order to increase the reach of actions and activities that can be carried out in different contexts, mobilizing and involving society, generating beneficial behaviors to the environment. Also, this will help understanding the current socio-environmental problems present in society and contributing to the creation of a new paradigm of relationship between human beings and the environment. This can be achieved, for example, from the systematic construction of a roadmap focused on values, in which there is a planning of activities in the practices of Environmental Education projects and programs that intentionally address the dimension of ethical and aesthetic values. Besides, it is possible to work on themes related to values integrating Environmental Education to technology by means of an interactive script via a gamified application.